Anxiety, depression, and academic stress among medical students during the COVID-19 pandemic - Avila-Carrasco, Lorena; Díaz-Avila, Daisy Lorena; Reyes-López, Adrian; Monarrez-Espino, Joel; Garza-Veloz, Idalia; Velasco-Elizondo, Perla; Vázquez-Reyes, Sodel; Mauricio-González, Alejandro; Solís-Galván, Jorge Alfonso; Martinez-Fierro, Margarita L. (Frontiers in Psychology, 2023)
Background The social distancing policies implemented by the health authorities during the COVID-19 pandemic in Mexico and elsewhere led to major changes in teaching strategies for college undergraduates. So far, there is limited data regarding the impact of the lockdown on the academic stress and mental health of these students. Objective To assess the occurrence of academic difficulties, anxiety, depression, and academic stressors resulting in somatization with subsequent coping strategies linked to the pandemic. Materials and methods A cross-sectional study was conducted with 728 medical students (years 1–5). A purposely designed questionnaire to assess academic difficulties associated with the pandemic was administered electronically. The validated Goldberg anxiety and depression scale was also used, as well as the SISCO-II inventory on academic stress. Results Screening for anxiety and depression led to a prevalence of 67.9 and 81.3%, respectively. Most relevant stressors, reported always or nearly always, included professors’ evaluations (63.9%), and reading overload of academic papers (50.6%). Factorial analyses showed that women were more prone to stress than men (p < 0.001). Somatization symptomatology included drowsiness or increased need of sleep, anxiety, anguish, desperation, chronic fatigue, and sleep disorders. Common coping strategies included practicing a hobby, done always or nearly always by 65% of students with high stress, and 34% of those with low stress (p < 0.001). Conclusion There was a relevant impact of the mandatory lockdown during COVID-19 pandemic on the mental health of medical students reflected in the high prevalence rates of anxiety, depression, and stressors in the studied population pointing to the need for designing and implementing preventive strategies to deal with the effects of lockdowns.